EFEKTIVITAS IMPLEMENTASI BANTUAN LANGSUNG TUNAI DI MASA PANDEMI COVID-19 (Studi Kasus Kelurahan Srimartani, Kabupaten Bantul) - Imam Al Fatiri, imam; Katon Mahendra, Gery (UIR PRESS, 2023)
The COVID-19 pandemic has triggered a major impact on the economy. There are three groups most affected by COVID-19, namely the Poor, Vulnerable Poor and Informal Workers. In order to improve welfare, the government provides social services or social security in the form of direct cash assistance. The purpose of this study is to identify, analyze and provide recommendations for the implementation of direct cash assistance during the COVID-19 pandemic (case study in Srimartani Village). This study is a descriptive qualitative study using employed observation, interviews and documentation method. The results of the study showed that the direct cash assistance was appropriately given to the community in need, meaning that this assistance could be used properly by the recipient. However, the organizers still needed to improve the recipient's data a lot, so that there were no data errors or duplicate data, and there was a need for special planning for the beneficiaries of direct cash assistance-Covid so that in the future they can be more independent and empowered when the assistance ends and they will not become dependent on assistance from the government. Besides, the recommendations given are, namely 1). there is a need for coordination between the central government and its recipient data with local governments, 2). there should be updating of integrated social welfare data on a regular basis, 3). community-based empowerment programs in handling the economic sector during the pandemic is needed.